Validation of the cutaneous impact location to predict intracranial lesion among elderly admitted to the Emergency Department after a ground-level fall. Issue 5 (May 2023) - Dubucs, Xavier; Lecuyer, Lucie; Balen, Frederic; Houze Cerfon, Charles Henri; Emond, Marcel; Lepage, Benoit; Colineaux, Hélène; Charpentier, Sandrine
Highlights: Falls are the leading cause of traumatic brain injury among the elderly. Almost one out of two head CT scans are carried out in Emergency Departments for traumatic brain injuries for elderly victims of ground level-falls. Nowadays, there is still no specific rule to predict intracranial lesion in this population. Our study validated a new determinant of intracranial lesion: the head cutaneous impact location. Our study supported that older patients receiving preinjury antiplatelets or anticoagulants were not associated with an increased risk of intracranial lesions. Abstract: Introduction: In the Emergency Departments, almost one out of two head CT scans are carried out for traumatic brain injuries among elderly victims of ground level-falls. Recently, a new predictive factor for intracranial lesions in this population has been suggested: presence and location of cutaneous impact. The aim of this study was to establish determinants of intracranial lesion among older patients admitted to EDs due to ground-level falls with traumatic brain injury using the head cutaneous impact location. Methods: A retrospective, observational and monocentric study of patients admitted to Emergency Department for ground-level falls with traumatic brain injury was carried out between 01 January 2017 and 31 July 2017. The primary outcome was identification of an acute intracranial lesion. A bootstrap procedure was employed to evaluate performance and internal validity of the final model. Results: Among the 1036 patients included, the mean age was 85.6 (SD 7.6) years and 94/1036 (9.1%, 95% CI 7.4–10.9) patients presented with an acute intracranial lesion. Multivariable analysis adjusted by bootstrap shrinkage showed that compared with temporal-parietal or occipital impact, Odds Ratio of intracranial lesions were 0.61 (95% CI 0.39–0.95, p  = 0.03) in patients with frontal impact, 0.27 (95% CI 0.12–0.59, p  = 0.001) in patients with facial impact and 0.21 (95% CI 0.06–0.77, p  = 0.018) in patients without cutaneous impact. Subcutaneous hematoma (OR 1.97, p  = 0.007), loss of consciousness (OR 4.66, p <0.001), fall-related amnesia (OR 2.58, p  = 2.6), vomiting (OR 2.62, p  = 0.002) and altered Glasgow Score (OR 6.79, p <0.001) were as well associated with high risk of intracranial lesion. Taking antiplatelets or anticoagulants were not associated with an increased risk of intracranial lesions. The model discrimination was adequate (C-statistic 0.79; 95% CI 0.73 – 0.85). Conclusion: Our results establish specific determinants of intracranial lesions among elderly after ground level-falls. The cutaneous impact location may identify patients with high risk of intracranial lesion. Further researches are needed to propose a specific score based on these determinants so as to better target Head CT scan use.